Tax evasion, minimum wage non-compliance and informality - Arnab K. Basu; Nancy Chau; Zahra Siddique (Institute for the Study of Labor (IZA), 2011)
We study the impact of tax and minimum wage reforms on the incidence of informality. To gauge the incidence of informality, we use measures of the extent of tax evasion, the extent of minimum wage non-compliance, and the size of the informal workforce. Our approach allows us to examine (i) the distinction between determinants of firm-level reported wage distribution and actual wage distribution, (ii) the complementarity of tax and minimum wage enforcement, (iii) the impact that a minimum wage reform has on tax and minimum wage compliance, and (iv) the impact that a tax policy reform has on tax and minimum wage compliance. We conclude with the design of optimal minimum wage and tax policies (even in the complete absence of minimum wage enforcement). We do so based on two objectives derived from popular concerns associated with an unchecked expansion of informality: tax revenue maximization, and poverty alleviation among workers.
urn:nbn:de:101:1-201201114034
Keywords: J3; J6; O17; 330; tax evasion; minimum wage reform; flat tax reform; poverty; informality; Mindestlohn; Normbefolgung; Steuerkriminalität; Schwarzarbeit; Steuerreform; Schwarzarbeit; Theorie